Channel Analysis and Marketing Margin of Cayenne Pepper (Capsicum frutescens L.) in Bumirestu Village, Wasile District, East Halmahera Regency - A. Marsaoly, Hasrul; Ekaria, Ekaria; Fitriyanto, Ahmad (Agrikan Jurnal Agribisnis Perikanan, 2022)
A marketing channel is a process of delivering goods and services from producers to consumers involving various parties. Similar to the marketing of cayenne pepper, generally the production of cayenne pepper produced by farmers is not influenced by the power when the price occurs during the marketing function. This study aims to determine the marketing information and marketing margins of cayenne pepper obtained from each marketing channel, as well as the advantages and disadvantages of each marketing institution. This research was conducted in Bumirestu Village, Wasile District, East Halmahera Regency with descriptive quantitative methods. The number of samples in this study was 38 respondents, consisting of 30 farmers, 4 collectors, and 4 traders. The results showed that the marketing channel of cayenne pepper in Bumirestu Village, Wasile District, East Halmahera Regency, there are two forms of marketing channels. Marketing channel I, namely from farmers - retailers - consumers, and marketing channel II, namely from farmers - collectors - retailers - consumers. The marketing margin in the marketing channel I am Rp. 5,000 and the marketing margin in marketing channel II is Rp. 10,000. Meanwhile, profit sharing in marketing channel I am 85.71%, and in the marketing channel, II is 75%. Furthermore, the profit ratio in each marketing agency, where channel I am 4.63 farmers, and 6.35 retailers. Channel II is 5.78 farmers, 9.79 collectors, and 8.67 retailers. Judging from all these marketing institutions, the highest profit-to-cost ratio is the middleman